Evaluation of linseed oil oleogels to partially replace pork backfat in fermented sausages. (29th October 2019) - Franco, Daniel; Martins, Artur J; López‐Pedrouso, María; Cerqueira, Miguel A; Purriños, Laura; Pastrana, Lorenzo M; Vicente, António A; Zapata, Carlos; Lorenzo, José M
Abstract: BACKGROUND: Nowadays, fat replacement in meat products is a matter of concern in the meat industry. The objective of this study was to evaluate the replacement of pork backfat with two oleogels of linseed in dry‐cured sausages. RESULTS: Five batches of dry‐cured sausages were prepared with two oleogels, a mixture of γ ‐oryzanol and β ‐sitosterol (SO) and beeswax (B), at two levels of replacement (20% and 40%) (SO‐20, SO‐40, B‐20, and B‐40, respectively) and a control batch. The fatty acid profile improved in terms of nutrition: the polyunsaturated fatty acid / saturated fatty acid (PUFA/SFA) and n‐6/n‐3 ratio was about 1.41 and 0.93 for the higher levels of replacement, SO‐40 and B‐40, respectively. Quality parameters such as pH and color also changed with the inclusion of oleogels, resulting in changes in the sensory quality. CONCLUSION: Oleogels based on linseed enabled the replacement of pork backfat in fermented sausages. Depending on the level of fat substitution, such oleogels could replace fat in dry‐cured sausages at the industrial level. © 2019 Society of Chemical Industry